IMPLEMENTASI PENDEKATAN STEAM UNTUK MENGEMBANGKAN KREATIVITAS ANAK TK - RAHMAWATI, RIYAS; AHYANA, IZZA (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2024)
The STEAM approach is a learning approach that encourages students to think more broadly about science, technology, engineering, art and mathematics which is packaged in fun and inspiring integrated learning activities. The objectives of this research are 1) Describe the implementation of the STEAM approach to develop children's creativity. 2) Describe the supporting and inhibiting factors in implementing the STEAM approach to develop children's creativity. This research uses a qualitative research approach and field research type. The location of this research is Kindergarten ABA 4 Jember. Determining informants using purposive techniques. Data collection techniques used non-participant observation, semi-structured interviews and documentation. Data analysis uses descriptive qualitative with an interactive model, namely: data condensation, data presentation, and drawing conclusions. Data triangulation uses source triangulation and technique triangulation. The results of this research are: 1) Implementation of the STEAM approach to develop the creativity of children aged 5-6 years at Kindergarten ABA 4 Jember, namely involving all students actively in learning which includes components of Science, Technology, Engineering, Art, and Mathematics to explore, discover and carry out experiments in a lesson. Before implementation, 12 children were at the Early Development stage, 12 children were Developing, and 21 children were Capable. Then, after implementing STEAM, the children experienced creative development, namely 4 children were at the Early Development stage, 13 children were Developing, and 28 children were Capable. 2) Supporting factors: educators have linear teacher education qualifications and have adequate resources. Meanwhile, inhibiting factors: lack of teacher training and skills, as well as lack of parental attention to the development of children's creativity. ABSTRAKPendekatan STEAM merupakan pendekatan pembelajaran yang mendorong anak didik dalam berpikir lebih luas tentang sains, teknologi, teknik, seni dan matematika yang dikemas dalam kegiatan pembelajaran yang terintegrasi menyenangkan, serta menginspirasi. Tujuan penelitian ini adalah 1) Mendeskripsikan Implementasi pendekatan STEAM untuk mengembangkan kreativitas anak. 2) Mendeskripsikan faktor pendukung dan penghambat dalam Implementasi pendekatan STEAM untuk mengembangkan kreativitas anak. Penelitian ini menggunakan pendekatan penelitian kualitatif dan jenis penelitian lapangan. Lokasi penelitian ini di TK ABA 4 Jember. Penentuan informan menggunakan teknik purposive. Teknik pengumpulan data menggunakan observasi nonpartisipan, wawancara semi terstruktur dan dokumentasi. Analisis data menggunakan deskriptif kualitatif dengan model interaktif yaitu: kondensasi data, penyajian data, dan menarik kesimpulan. Triangulasi data menggunakan triangulasi sumber dan triangulasi teknik. Hasil penelitian ini adalah: 1) Implementasi pendekatan STEAM untuk mengembangkan kreativitas anak usia 5- 6 tahun di TK ABA 4 Jember yaitu melibatkan semua peserta didik secara aktif dalam pembelajaran yang meliputi komponen Science, Technology, Engineering, Art, and Mathematics untuk bereksplorasi, menemukan serta melakukan percobaan dalam suatu pembelajaran. Sebelum diterapkan, ada 12 anak berada pada tahap Awal Perkembangan, 12 anak Berkembang, dan 21 anak Cakap. Kemudian setelah menerapkan STEAM anak mengalami perkembangan kreativitas yaitu 4 anak berada pada tahap Awal Perkembangan, 13 anak Berkembang, dan 28 anak Cakap. 2) Faktor pendukung: pendidik memiliki kualifikasi pendidikan guru yang linier serta memiliki sumber daya yang memadai. Sedangkan Faktor Penghambat: kurangnya pelatihan dan keterampilan guru, serta kurangnya perhatian orang tua terhadap perkembangan kreativitas anak.